The role of occupational physician in Italy during and after the COVID-19 pandemic: A Position paper by the Italian Association of Psychology and Occupational Health (AIPMEL) - Francesco CHIRICO; Angelo SACCO; Giuseppe FERRARI; AIPMEL (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
In this position paper, which is based on a review of literature, Italian regulations and international guidelines for the prevention of COVID-19 infection, the Italian Association of Psychology and Occupational health (AIPMEL) makes a proposal for a protocol that occupational physicians may use to tackle COVID-19 outbreaks in the workplaces during the pandemic and for preventing COVID-19 negative effects on physical and mental health of the workers after the pandemic, as well. In Italy, the Legislative Decree 9 April 2008, no.81 requires the health surveillance of the workers is carried out by an occupational physician, termed as “medico competente”, who has to be appointed by the employer, for cooperating with risk managers and occupational stakeholders to the risk assessment process and performing occupational health surveillance. In Italy, during the COVID-19 pandemic, the government released as Decrees issued by the President of Council a national protocol for the prevention, control and public health management of COVID-19 outbreaks in the workplaces, which is mandatory for all employers. We believe occupational health surveillance may be a useful instrument to verify the effectiveness of the risk assessment and preventive measures required by this protocol. Furthermore, occupational measures developed to prevent COVID-19 infection should be enacted on the basis of the risk assessment process. SARS-CoV-2 has been recently classified in the list of biological agents known to infect humans, as a risk group 3 human pathogen. For this reason, it may be considered as a “generic” (biological) risk factor only in certain workplaces (e.g. in the offices closed to the public or in the context of the “smartworking”), but in other working environments (e.g., essential workers including health and social care employees) SARS-CoV-2 represents a “specific” occupational risk factor. Therefore, in high-risk working environments, further and more stringent measures are needed, including occupational health surveillance for protecting “vulnerable” workers through vaccination programs and fitness for job examinations for the prevention of the biological risk according to article 279 of Legislative Decree no.81 of 2008. Workplace health programs are useful in all workplaces during and after the pandemic to promote better levels of mental well-being and support workers affected by long-COVID syndrome who return to work. Ultimately, occupational physicians and public health stakeholders may collaborate for carrying out the best practices for the COVID-19 prevention in the workplaces.